ASSESSMENT OF MALIR RIVER WATER QUALITY AND IT SUITABILITY FOR IRRIGATION PURPOSES - MUHAMMAD SALEEM (Journal of Engineering Studies and Research)
Malir river, which is passing through industrial area of mega city Karachi is assessed for the suitability of its water for irrigation purposes. It was found that the concentration of studied metals is a function of position and season. Most of the pollutants are within the limits provided by national and international standards however, nickel was above the allowable limit for irrigation water quality (1000 μg/L) which is probably attributed to the discharge of effluent from vegetable-ghee manufacturing factories working in the vicinity. The overall suitability of Malir river based on EC, TDS and SAR is ranked’Permissible’ for irrigation.